2022
DOI: 10.3390/pharmaceutics14112473
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Extraction with Cyclodextrins as a Way of Improving the Antidiabetic Activity of Actinidia Leaves

Abstract: Five varieties of Actinidia leaves (Geneva, Jumbo, Ken’s Red, Kijivska Hibridna, and Sentyabraskaya) were analyzed. The profiles of active compounds were determined, namely quercetin, rutin, epicatechin, chlorogenic acid, and kaempferol, in the raw material. Suspecting that the raw material might prove important in the treatment of diabetes, the authors assessed the antioxidant activity and the ability to inhibit enzymes responsible for the development of diabetes (α-glucosidase and α-amylase). As a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The inhibition of α-glucosidase activity was studied on the basis of the method of Sip et al [ 44 ] with minor modifications. A total of 50 μL of 0.1 M phosphate buffer (pH 6.8), 50 μL of the sample, prepared similarly to the solubility test, and 30 μL of α-glucosidase solution (0.5 U·mL −1 ) were added to wells of a 96-well microplate.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition of α-glucosidase activity was studied on the basis of the method of Sip et al [ 44 ] with minor modifications. A total of 50 μL of 0.1 M phosphate buffer (pH 6.8), 50 μL of the sample, prepared similarly to the solubility test, and 30 μL of α-glucosidase solution (0.5 U·mL −1 ) were added to wells of a 96-well microplate.…”
Section: Methodsmentioning
confidence: 99%
“…The stability constant ( K st ) equals 994.2 M -1 . It was reported that K s value between 50 and 5000 M −1 was considered the most suitable for the improvement of solubility and stability of poorly soluble drugs [ 23 ]. In conclusion, HPβCD increased the solubility of AP significantly with good stability of the complex in a ratio 1:1 host-guest molecules.…”
Section: Resultsmentioning
confidence: 99%
“…For the CUPRAC assay, following the Gościniak et al method [ 123 ], an amount of 50.0 µL of each sample solution and 150.0 µL of the CUPRAC reagent was pipetted onto the plate and incubated for 30 min at room temperature in darkness. For the FRAP assay, following the Sip et al method [ 124 ], the mixture of 25.0 µL of each sample solution and 175.0 µL of FRAP mixture was incubated for 30 min at 37 °C in dark conditions. Then, the absorbance was measured at 450 nm (CUPRAC assay) and 593 nm (FRAP assay) using a plate reader (Multiskan GO, Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%